Analysis on the Effectiveness of Personal Protective Equipment in Protecting Against Transmission of COVID-19 – A Systematic Review with Additional Insights on Vaccinated Population - Brenda Carolinsia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
COVID-19 is transmitted through respiratory droplet through close contact. The risk of transmission is even higher in aerosol-generating procedures, as there are evidences that the disease could be transmitted airborne in these particular settings. Personal protective equipment remains the most effective way to prevent transmission of COVID-19. In this systematic review, we aim to synthesize data on the effectiveness of personal protective equipment in protecting against transmission of COVID-19. We also added additional insight the benefits of effective PPE use towards the hospital services, and on whether these protective measures should still be followed in post-vaccination population. We conducted a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Four internet databases were searched using predefined search terms. Narrative review was developed on the effectiveness of personal protective equipment in protecting against transmission of COVID-19. Out of initial 71 articles found using the predefined search terms, 8 studies fulfilled the inclusion criteria and were included in our final analysis. We found that face masks remain the most effective personal protective equipment against the transmission of COVID-19. Respirator masks such as the N95 mask offer better protection compared to regular cloth face mask, but is equal to or only to slightly better compared to surgical masks. Other effective protective equipment includes gowns, gloves, and eye protection such as face shields or goggles for aerosol-generating procedures. Face masks is highly effective in protecting against the transmission of COVID-19, with surgical mask and respirator mask provide better protection compared to cloth masks. Gowns, gloves, and eye protection were needed for aerosol-generating procedures. In a world with only a small number of people are vaccinated against COVID-19, it remains important that personal protective equipment should still be worn to prevent transmission.